Dens invaginatus u odontoma dilatado, controversia de una definición. Una revisión de la literatura - Coria-Bello, Mayra (2021)
The invaginate tooth (IT) is an alteration in the development of the dental organ, which occurs as a consequence of invagination of the internal epithelium of the enamel organ. IT is also known as “dens in dente”, among other denominations, and presents a series of clinical, histological and imaging characteristics. The most extreme variant of IT has a very complex configuration, and the magnitude of the intussusception has led to it also being called dilated odontoma, being a term that generates confusion in some professionals. While the term odontoma has been reported as a synonym for both IT as well as a new variant of odontomas, there is a difference betweene the two types: one is a developmental anomaly, and the other is a growth with a hamartomatous appearance. However, the literature continues to use both terms to define IT, and thus, it is important to know the origin and be aware that the controversy is based on historical and customary references.